Beaumaris Castle - Master James of St. George
On the landward side of Beaumaris Castle, thee was a second entrance complete with a gatehouse for its defense. In this, the square gate tower was amalgamated with two flanking towers to form a rectangular block with two projecting semicircular wings facing the field. This form later became the standard gatehouse plan.